Novel recoverable paint and application thereof

By combining modified epoxy resin with multiple components, a recyclable paint is constructed, which solves the problems of paint being difficult to recycle and having insufficient self-healing ability. This achieves long-term protection and self-healing of the coating, making it suitable for aerospace, automotive bodies, and electrical equipment.

CN121293843APending Publication Date: 2026-01-09GUANGXI NANNING WEIYI ANTISEPTIC TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511838318.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-12-08
Publication Date
2026-01-09

AI Technical Summary

Technical Problem

Existing paints are difficult to recycle at the end of their life cycle and have limited self-healing capabilities, making them unsuitable for long-term stable application in harsh environments.

Method used

By employing components such as modified epoxy resin, reactive diluent, amino-modified multi-walled carbon nanotubes, flake zinc powder, corrosion-responsive capsules, and curing capsules, a reversible cross-linked network is constructed through synergistic effects, enabling the coating to achieve recyclability and self-healing capabilities.

Benefits of technology

It enables intelligent sensing, proactive repair, and on-demand recycling of paint, significantly improving resource utilization and reducing total lifecycle costs. It is suitable for long-term protection of aerospace, automotive bodies, and electrical equipment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The invention relates to the field of high polymer materials and coatings, in particular to recoverable novel paint and application thereof.The recoverable novel paint is prepared from, by mass, 40-50 parts of modified epoxy resin, 5-10 parts of reactive diluent, 12-18 parts of bismaleimide, 1-3 parts of amino modified multi-walled carbon nanotubes, 5-10 parts of flaky zinc powder and 8-12 parts of corrosion response capsules. The prepared novel paint has multiple functions of intelligent sensing, active repairing and on-demand recycling, compared with the prior art, the industrial problems that a traditional high-performance coating is unrecyclable, single in self-repairing capacity and unrepeatable are effectively solved, the resource utilization rate is remarkably increased, the whole life cycle cost is reduced, and the application prospect is wide. The product has a wide application prospect in the fields with strict requirements on reliability and sustainability, such as aerospace, high-end equipment remanufacturing, new energy infrastructure, precision electronics and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of polymer materials and coatings, and more particularly to a novel recyclable paint and its applications. Background Technology

[0002] Paint is a material that forms a solid film by being coated on the surface of an object, serving to decorate, protect, or impart special functions. With the deepening of the concept of sustainable development, new types of paint with recyclable characteristics have emerged. These paints can achieve overall peeling of the coating or repolymerization of the resin at the end of their life cycle, thereby reducing resource consumption and waste. In fields such as high-end equipment remanufacturing, green packaging, and precision electronic protection, these materials show broad application prospects.

[0003] Current research mainly focuses on endowing coatings with repair or recycling capabilities. Early attempts involved adding thermoplastic resins or encapsulating microcapsules containing repair agents in coatings. These methods can achieve a certain degree of repair or deformation under external stimuli, but they usually reduce the weather resistance and mechanical strength of the coating and cannot achieve chemical-grade recycling of the resin. Subsequent research has shifted to introducing dynamic covalent bond structures, enabling the coating to undergo reversible cross-linking under heat or light. This provides the possibility for the theoretical recycling of materials. However, such systems often face problems such as harsh reversible conditions and insufficient long-term stability, making them difficult to apply in harsh environments such as actual corrosion protection.

[0004] Therefore, there is a need to design a new type of recyclable paint and its applications. Summary of the Invention

[0005] In view of this, the purpose of this invention is to provide a novel recyclable paint and its application to solve the problems raised in the prior art.

[0006] To achieve the above objectives, the present invention provides a novel recyclable paint, comprising the following components in parts by weight: 40-50 parts modified epoxy resin, 5-10 parts reactive diluent, 12-18 parts bismaleimide, 1-3 parts amino-modified multi-walled carbon nanotubes, 5-10 parts flake zinc powder, 8-12 parts corrosion-responsive capsules, 5-8 parts curing capsules, 0.5-1.5 parts wetting and dispersing agent, 0.1-0.2 parts leveling agent, 0.2-0.8 parts defoamer, and 3-8 parts zinc phosphate pigment; The modified epoxy resin is a furfurylamine-modified epoxy resin; The wetting and dispersing agent is BYK-163; The leveling agent is a polyacrylate solution; The defoamer is BYK-055.

[0007] Furthermore, the preparation steps of the modified epoxy resin are as follows: Under a nitrogen atmosphere, triphenylphosphine catalyst and anhydrous propylene glycol methyl ether acetate solvent were added to epoxy resin and stirred at 200-300 rpm for 20-30 min. Furfurylamine was added, the temperature was raised to 60-70℃, and the reaction was stirred at 300-400 rpm for 4-6 h to obtain a mixture. The mixture was then cooled to 60-70℃ and vacuum dried for 2-4 h to obtain modified epoxy resin. The mass ratio of the epoxy resin, anhydrous propylene glycol methyl ether acetate solvent, and triphenylphosphine catalyst is 1:0.2-0.3:0.003-0.005; The synergistic effect of triphenylphosphine catalyst and anhydrous propylene glycol methyl ether acetate solvent significantly improved the reaction efficiency and product uniformity, ensuring the high purity, high functionality and excellent storage stability of the modified epoxy resin, laying a solid foundation for the subsequent construction of reversible crosslinking network.

[0008] Furthermore, the preparation steps of the reactive diluent are as follows: Furfuryl alcohol and the catalyst tetrabutylammonium bromide were added to epichlorohydrin, heated to 63-67℃, stirred at 300-350 rpm for 3-4 hours until the reaction was complete, cooled to 0-4℃, and 30wt% sodium hydroxide solution was added. The mixture was stirred at 400-500 rpm for 1-2 hours, heated to 25-30℃, and stirred for 2-3 hours. Deionized water was added, and the mixture was stirred at 200-250 rpm for 12-14 hours. The mixture was then vacuum distilled to obtain the active diluent. The mass ratio of furfuryl alcohol, tetrabutylammonium bromide catalyst, epichlorohydrin, 30wt% sodium hydroxide solution, and deionized water is 1:0.04-0.05:1.3-1.4:3-4:4-5; This step achieves efficient and homogeneous Williamson ether synthesis via furfuryl alcohol and epichlorohydrin in the presence of tetrabutylammonium bromide catalyst, significantly improving the synthesis yield and epoxy group purity of the reactive diluent, and providing a key diluent component with high reactivity for paint systems.

[0009] Furthermore, the preparation steps of the corrosion-responsive capsule are as follows: Step A1: Add gelatin and gum arabic to deionized water, heat to 50-54℃, stir at 100-200 rpm for 10-12 minutes, add 1wt% glacial acetic acid to adjust the pH to 4-4.5, add Tween-80 to obtain the aqueous phase; Step A2: Add benzotriazole and monomaleimide monomers to ethyl acetate, stir at 100-200 rpm for 10-12 min to obtain the oil phase; Step A3: Add the oil phase to the aqueous phase, stir at 1000-1500 rpm for 10-16 min, add deionized water, heat to 50-54℃, stir at 400-450 rpm for 10-12 min, cool to 8-10℃, add 25wt% glutaraldehyde solution, stir at 400-500 rpm for 2-4 h, add sodium hydroxide to adjust the pH to 9.0-9.5, stir for 1-1.2 h, wash, filter, and vacuum dry for 22-24 h to obtain corrosion-responsive capsules; In this step, gelatin provides cationic properties, while gum arabic contributes anionic framework. Under acidic conditions, they co-deposit on the surface of oil droplets through electrostatic interaction, forming a uniform and dense composite capsule wall. The synergy between the two ensures the integrity of the microcapsule structure and precise responsiveness to alkaline environments, providing the coating with long-lasting and triggerable self-healing capabilities.

[0010] Further, the mass ratio of gelatin, gum arabic, and Tween-80 in step A1 is 1:1-1.2:0.05-0.07; The mass ratio of benzotriazole, monomaleimide monomer to ethyl acetate in step A2 is 1:0.3-0.4:10-12; The mass ratio of the oil phase, aqueous phase, deionized water, and 25wt% glutaraldehyde solution in step A3 is 1:9-10:8-9:0.05-0.06.

[0011] Furthermore, the solidified capsule preparation steps are as follows: Step B1: Add urea to a 37wt% formaldehyde solution, add 10wt% sodium hydroxide solution to adjust the pH to 8.0-8.5, heat to 65-75℃, stir at 300-400 rpm for 1-1.2 hours to obtain urea-formaldehyde resin prepolymer; Step B2: Add sodium dodecylbenzenesulfonate to deionized water, add 2wt% polyvinyl alcohol solution, stir at 100-200 rpm for 10-12 hours to obtain an emulsified aqueous phase; Step B3: Add the boron trifluoride-monoethylamine complex to dibutyl phthalate, add the emulsified aqueous phase, stir at 1500-2000 rpm for 10-12 min, heat to 50-60℃, add urea-formaldehyde resin prepolymer, add 10wt% ammonium chloride solution to adjust the pH to 3.5-4.0, add resorcinol, stir at 300-500 rpm for 2-3 h, wash, filter, and vacuum dry for 22-24 h to obtain cured capsules; In this step, urea and resorcinol play a key synergistic role under acidic conditions. Urea provides the main wall material skeleton, while resorcinol, as a highly efficient modified crosslinking agent, significantly enhances the crosslinking density and wall material compactness of urea-formaldehyde resin. The synergy between the two ensures that the microcapsule wall has excellent mechanical strength and sealing performance, which can not only stably protect the capsule core, but also rupture sensitively under construction shear force and accurately trigger the curing reaction.

[0012] Further, the mass ratio of urea to 37wt% formaldehyde solution in step B1 is 1:2-3; In step B2, the mass ratio of sodium dodecylbenzenesulfonate, deionized water, and 2wt% polyvinyl alcohol solution is 1:300-350:100-120. The mass ratio of boron trifluoride-monoethylamine complex, dibutyl phthalate, emulsified aqueous phase, urea-formaldehyde resin prepolymer, and resorcinol in step B3 is 1:5-6:40-50:10-12:0.02-0.03.

[0013] A method for preparing a novel recyclable paint, comprising the following steps: Step S1: Add BYK-163 to modified epoxy resin a, heat to 25-35℃, stir at 300-500 rpm for 3-5 minutes, add amino-modified multi-walled carbon nanotubes and flake zinc powder, stir at 2500-3000 rpm for 20-30 minutes to obtain slurry; Step S2: Add modified epoxy resin b, reactive diluent and bismaleimide to the slurry, rotate at 1000-1200 rpm, heat to 25-35℃, stir for 16-20 minutes to obtain the base paint; Step S3: Add the corrosion-responsive capsules and curing capsules to the base paint, stir at 150-300 rpm for 10-16 min, add polyacrylate solution, BYK-055 and zinc phosphate pigment, stir for 10-12 min, reduce the pressure to -0.09 to -0.095 MPa, stir at 300-500 rpm for 10-16 min, and pass through a 150-mesh sieve to obtain a recyclable new paint. This step imparts recyclability to the coating through modified epoxy resin and bismaleimide, while carbon nanotubes and flake zinc powder construct an efficient physicochemical anti-corrosion barrier. The dual microcapsules respectively achieve corrosion-responsive self-healing and construction-triggered curing. The components are precisely matched in space and function, ultimately achieving a unified solution of long-term coating protection, damage self-healing, and complete recyclability.

[0014] Further, in step S1, the mass ratio of BYK-163, modified epoxy resin a, amino-modified multi-walled carbon nanotubes and flake zinc powder is 1:25-27:2-3:7-9; In step S2, the mass ratio of the modified epoxy resin b, reactive diluent, bismaleimide, and slurry is 1:0.2-0.4:0.5-0.7:1.3-1.5. The mass ratio of the corrosion-responsive capsule, curing capsule, base paint, polyacrylate solution, BYK-055, and zinc phosphate pigment in step S3 is 1:0.6-0.7:8-9:0.02-0.04:0.02-0.04:0.5-0.6.

[0015] Applications of a novel recyclable paint, wherein the novel recyclable paint is used in aerospace equipment, high-end automobile bodies and chassis, and electrical equipment housings.

[0016] The beneficial effects of this invention are: This invention provides a novel recyclable paint and its preparation and application methods. The novel paint prepared by this invention has multiple functions including intelligent sensing, active repair, and on-demand recycling. Compared with existing technologies, it effectively solves the industry problems of traditional high-performance coatings being non-recyclable, having limited self-healing capabilities, and being non-repeatable. It significantly improves resource utilization and reduces the total life cycle cost. This product has broad application prospects in fields with stringent requirements for reliability and sustainability, such as aerospace, high-end equipment remanufacturing, new energy infrastructure, and precision electronics. Detailed Implementation

[0017] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail below with reference to specific embodiments.

[0018] Example 1: Preparation of a modified epoxy resin Under a nitrogen atmosphere, 3g of triphenylphosphine catalyst and 300g of anhydrous propylene glycol methyl ether acetate solvent were added to 1000g of epoxy resin. The mixture was stirred at 200 rpm for 30 min, then furfurylamine was added. The mixture was heated to 60℃ and stirred at 400 rpm for 4 h to obtain a mixture. The mixture was then cooled to 70℃ (the amino group of furfurylamine undergoes a ring-opening addition reaction with the epoxy group of the epoxy resin, which is a moderate to significant exothermic reaction), and vacuum dried for 2 h to obtain the modified epoxy resin.

[0019] Example 2: Preparation of a modified epoxy resin Under a nitrogen atmosphere, 4g of triphenylphosphine catalyst and 250g of anhydrous propylene glycol methyl ether acetate solvent were added to 1000g of epoxy resin. The mixture was stirred at 250 rpm for 25 min, then furfurylamine was added. The mixture was heated to 65℃ and stirred at 350 rpm for 5 h to obtain a mixture. The mixture was then cooled to 65℃ (the amino group of furfurylamine undergoes a ring-opening addition reaction with the epoxy group of the epoxy resin, which is a moderate to significant exothermic reaction), and vacuum dried for 3 h to obtain the modified epoxy resin.

[0020] Example 3: Preparation of a modified epoxy resin Under a nitrogen atmosphere, 5g of triphenylphosphine catalyst and 200g of anhydrous propylene glycol methyl ether acetate solvent were added to 1000g of epoxy resin. The mixture was stirred at 300 rpm for 20 min, then furfurylamine was added. The mixture was heated to 70℃ and stirred at 300 rpm for 6 h to obtain a mixture. The mixture was then cooled to 60℃ (the amino group of furfurylamine undergoes a ring-opening addition reaction with the epoxy group of the epoxy resin, which is a moderate to significant exothermic reaction), and vacuum dried for 4 h to obtain the modified epoxy resin.

[0021] Example 4: Preparation of an active diluent 100g of furfuryl alcohol and 4g of tetrabutylammonium bromide catalyst were added to 140g of epichlorohydrin. The mixture was heated to 63℃ and stirred at 350rpm for 3 hours until the reaction was complete. The mixture was then cooled to 4℃, and 300g of 30wt% sodium hydroxide solution was added. The mixture was stirred at 500rpm for 1 hour, then heated to 30℃ and stirred for 2 hours. Finally, 500g of deionized water was added and stirred at 200rpm for 14 hours. The mixture was then vacuum distilled to obtain the active diluent.

[0022] Example 5: Preparation of an active diluent 100g of furfuryl alcohol and 4.5g of tetrabutylammonium bromide catalyst were added to 135g of epichlorohydrin. The mixture was heated to 65℃ and stirred at 325rpm for 3.5h until the reaction was complete. The mixture was then cooled to 2℃, and 350g of 30wt% sodium hydroxide solution was added. The mixture was stirred at 450rpm for 1.5h, heated to 27℃, and stirred for 2.5h. Finally, 450g of deionized water was added and stirred at 225rpm for 13h. The mixture was then vacuum distilled to obtain the active diluent.

[0023] Example 6: Preparation of an active diluent 100g of furfuryl alcohol and 5g of tetrabutylammonium bromide catalyst were added to 130g of epichlorohydrin. The mixture was heated to 67℃ and stirred at 300rpm for 4 hours until the reaction was complete. The mixture was then cooled to 0℃, and 400g of 30wt% sodium hydroxide solution was added. The mixture was stirred at 400rpm for 2 hours. The mixture was then heated to 25℃ and stirred for 3 hours. 400g of deionized water was added and stirred at 250rpm for 12 hours. The mixture was then vacuum distilled to obtain the active diluent.

[0024] Example 7: Preparation of a corrosion-responsive capsule S1: Add 100g of gelatin and 120g of gum arabic to 1000mL of deionized water, heat to 54℃, stir at 100rpm for 12min, add 1wt% glacial acetic acid to adjust the pH to 4-4.5, add 5g of Tween-80 to obtain the aqueous phase. S2: Add 10g of benzotriazole and 3g of monomaleimide monomer to 120g of ethyl acetate, stir at 100rpm for 12min to obtain the oil phase; S3: Add 100g of oil phase to 900g of aqueous phase, stir at 1500rpm for 10min, add 900g of deionized water, heat to 50℃, stir at 450rpm for 10min, cool to 10℃, add 5g of 25wt% glutaraldehyde solution, stir at 500rpm for 2h, add sodium hydroxide to adjust pH to 9.0-9.5, stir for 1.2h, wash, filter, and vacuum dry for 22h to obtain corrosion-responsive capsules.

[0025] Example 8: Preparation of a corrosion-responsive capsule S1: Add 100g of gelatin and 110g of gum arabic to 1000mL of deionized water, heat to 52℃, stir at 150rpm for 11min, add 1wt% glacial acetic acid to adjust the pH to 4-4.5, add 6g of Tween-80 to obtain the aqueous phase. S2: Add 10g of benzotriazole and 3.5g of monomaleimide monomer to 110g of ethyl acetate, stir at 150rpm for 11min to obtain the oil phase; S3: Add 100g of oil phase to 950g of aqueous phase, stir at 1250rpm for 13min, add 850g of deionized water, heat to 52℃, stir at 425rpm for 11min, cool to 9℃, add 5.5g of 25wt% glutaraldehyde solution, stir at 450rpm to react for 3 minutes, add sodium hydroxide to adjust pH to 9.0-9.5, stir for 1.1h, wash, filter, and vacuum dry for 23h to obtain corrosion-responsive capsules.

[0026] Example 9: Preparation of a corrosion-responsive capsule S1: Add 100g of gelatin and 120g of gum arabic to 1000mL of deionized water, heat to 50℃, stir at 200rpm for 10min, add 1wt% glacial acetic acid to adjust the pH to 4-4.5, add 7g of Tween-80 to obtain the aqueous phase. S2: Add 10g of benzotriazole and 4g of monomaleimide monomer to 100g of ethyl acetate, stir at 200rpm for 10min to obtain the oil phase; S3: Add 100g of oil phase to 1000g of aqueous phase, stir at 1000rpm for 16min, add 800g of deionized water, heat to 54℃, stir at 400rpm for 12min, cool to 8℃, add 6g of 25wt% glutaraldehyde solution, stir at 400rpm for 4h, add sodium hydroxide to adjust pH to 9.0-9.5, stir for 1h, wash, filter, and vacuum dry for 24h to obtain corrosion-responsive capsules.

[0027] Example 10: Preparation of a solidified capsule S1: Add 100g of urea to 200g of 37wt% formaldehyde solution, add 10wt% sodium hydroxide solution to adjust the pH to 8.0-8.5, heat to 75℃, stir at 300rpm for 1.2h to obtain urea-formaldehyde resin prepolymer; S2: Add 1g of sodium dodecylbenzenesulfonate to 300g of deionized water, add 120g of 2wt% polyvinyl alcohol solution, stir at 100rpm for 12h to obtain an emulsified aqueous phase; S3: Add 10g of boron trifluoride-monoethylamine complex to 50g of dibutyl phthalate, add 500g of emulsified aqueous phase, stir at 1500rpm for 12min, heat to 50℃, add 120g of urea-formaldehyde resin prepolymer, add 10wt% ammonium chloride solution to adjust pH to 3.5-4.0, add 0.2g of resorcinol, stir at 500rpm for 2h, wash, filter, and vacuum dry for 24h to obtain cured capsules.

[0028] Example 11: Preparation of a solidified capsule S1: Add 100g of urea to 250g of 37wt% formaldehyde solution, add 10wt% sodium hydroxide solution to adjust the pH to 8.0-8.5, heat to 60℃, stir at 350rpm for 1.1h to obtain urea-formaldehyde resin prepolymer; S2: Add 1g of sodium dodecylbenzenesulfonate to 325g of deionized water, add 110g of 2wt% polyvinyl alcohol solution, stir at 150rpm for 11h to obtain an emulsified aqueous phase; S3: Add 10g of boron trifluoride-monoethylamine complex to 55g of dibutyl phthalate, add 450g of emulsified aqueous phase, stir at 1750rpm for 11min, heat to 55℃, add 110g of urea-formaldehyde resin prepolymer, add 10wt% ammonium chloride solution to adjust pH to 3.5-4.0, add 0.25g of resorcinol, stir at 400rpm for 2.5h, wash, filter, and vacuum dry for 23h to obtain cured capsules.

[0029] Example 12: Preparation of a solidified capsule S1: Add 100g of urea to 300g of 37wt% formaldehyde solution, add 10wt% sodium hydroxide solution to adjust the pH to 8.0-8.5, heat to 65℃, stir at 400rpm for 1h to obtain urea-formaldehyde resin prepolymer. S2: Add 1g of sodium dodecylbenzenesulfonate to 350g of deionized water, add 100g of 2wt% polyvinyl alcohol solution, stir at 200rpm for 10h to obtain an emulsified aqueous phase; S3: Add 10g of boron trifluoride-monoethylamine complex to 60g of dibutyl phthalate, add 400g of emulsified aqueous phase, stir at 2000rpm for 10min, heat to 60℃, add 100g of urea-formaldehyde resin prepolymer, add 10wt% ammonium chloride solution to adjust pH to 4.0, add 0.2g of resorcinol, stir at 500rpm for 2h, wash, filter, and vacuum dry for 24h to obtain cured capsules.

[0030] Example 13: Preparation of a novel recyclable paint S1: Add 10g of BYK-163 to 250g of modified epoxy resin, heat to 35℃, stir at 300rpm for 5min, add 20g of amino-modified multi-walled carbon nanotubes and 90g of flake zinc powder, stir at 2500rpm for 30min to obtain slurry. S2: Add 200g of modified epoxy resin, 40g of reactive diluent and 140g of bismaleimide to 260g of slurry, rotate at 1200rpm, heat to 25℃, stir for 20min to obtain base paint. S3: Add 50g of corrosion-responsive capsules and 30g of curing capsules to 450g of base paint, stir at 150rpm for 16min, add 1g of polyacrylate solution, 2g of BYK-055 and 25g of zinc phosphate pigment, stir for 12min, reduce the pressure to -0.09MPa, stir at 500rpm for 10min, and pass through a 150-mesh sieve to obtain a recyclable new type of paint.

[0031] Example 14: Preparation of a novel recyclable paint S1: Add 10g of BYK-163 to 260g of modified epoxy resin, heat to 30℃, stir at 400rpm for 4min, add 25g of amino-modified multi-walled carbon nanotubes and 80g of flake zinc powder, stir at 2750rpm for 25min to obtain slurry. S2: Add 200g of modified epoxy resin, 60g of reactive diluent and 120g of bismaleimide to 280g of slurry, rotate at 1100rpm, heat to 30℃, stir for 18min to obtain base paint. S3: Add 50g of corrosion-responsive capsules and 32.5g of curing capsules to 425g of base paint, stir at 225rpm for 13min, add 1.5g of polyacrylate solution, 1.5g of BYK-055 and 27.5g of zinc phosphate pigment, stir for 11min, reduce pressure to -0.0925MPa, stir at 400rpm for 13min, and pass through a 150-mesh sieve to obtain a recyclable new type of paint.

[0032] Example 15: Preparation of a novel recyclable paint S1: Add 10g of BYK-163 to 270g of modified epoxy resin, heat to 25℃, stir at 500rpm for 3min, add 30g of amino-modified multi-walled carbon nanotubes and 70g of flake zinc powder, stir at 3000rpm for 20min to obtain slurry. S2: Add 200g of modified epoxy resin, 80g of reactive diluent and 100g of bismaleimide to 300g of slurry, rotate at 1000rpm, heat to 35℃, stir for 16min to obtain base paint. S3: Add 50g of corrosion-responsive capsules and 35g of curing capsules to 400g of base paint, stir at 300rpm for 10min, add 2g of polyacrylate solution, 1g of BYK-055 and 30g of zinc phosphate pigment, stir for 10min, reduce the pressure to -0.095MPa, stir at 300rpm for 16min, and pass through a 150-mesh sieve to obtain a recyclable new type of paint.

[0033] Comparative Example 1: Compared with Example 15, this comparative example only reduces the rotation speed from 2500 rpm to 800 rpm in the preparation process S1 of a recyclable novel paint. All other steps and parameters are the same, and will not be repeated here. The final result is a recyclable novel paint.

[0034] Comparative Example 2: Compared with Example 15, this comparative example only replaces "flaky zinc powder" with "ordinary spherical zinc powder (325 mesh)". All other steps and parameters are the same, and will not be repeated here. The final result is a recyclable new type of paint.

[0035] Comparative Example 3: This comparative example differs from Example 15 only in that it does not contain "polyacrylate solution". All other steps and parameters are the same, and will not be repeated here. The final result is a recyclable new paint.

[0036] Performance testing: Corrosion resistance test: Refer to the GB / T 1771-2022 testing standard: 1. Take a cold-rolled steel plate of 150mm×70mm×0.8mm, spray the recyclable new paint onto the steel plate using the air spraying method, cure at 120℃ for 30 minutes, seal the edges after cooling, and make a 50mm long scratch in the center that extends to the substrate to make a test plate. 2. Place the test plate with the scratches facing upwards at a 25° angle to the vertical direction in a salt spray chamber at a temperature of 35°C. Spray continuously with a sodium chloride solution of 50 g / L for 1000 hours. 3. After the test, use calipers to measure the maximum corrosion spread width on one side of the scratch. At the same time, refer to GB / T1766-2008 standard to evaluate the level of bubbles, rust and cracking of the coating in the unscratched area.

[0037] Table 1 Corrosion Resistance Test Results

[0038] Impact resistance test: Refer to the GB / T 17321-2020 testing standard: 1. Take a 120mm×50mm×0.3mm tinplate that meets the requirements of GB / T 9271, spray recyclable new paint onto the tinplate, cure for 7 days, and make a test sample. 2. Place the sample with the paint film facing up on the impact tester, and use a 1000g heavy hammer to drop it freely from 50cm to impact the sample; Use a magnifying glass to observe whether the paint film in the impact-deformed area is cracked or peeled.

[0039] Table 2 Impact resistance test results

[0040] Data Analysis: As can be seen from Tables 1-2, the recyclable novel paint prepared by this invention has excellent anti-corrosion and impact resistance properties, achieving a synergy between long-term protection and physical strength. This is due to its precisely designed components and processes, which achieve precise integration of space and function, thereby realizing the unity of long-term coating protection, self-healing of damage and complete recycling. In contrast, Comparative Example 1 reduced the high-shear dispersion speed to 800 rpm during the preparation process, resulting in uneven packing dispersion and significant performance degradation. This was because the shear force provided by the excessively low speed was insufficient to effectively open the agglomerates of amino-modified multi-walled carbon nanotubes and peel off the flake zinc powder. This caused severe agglomeration of the packing in the resin matrix, which not only failed to form a dense physical barrier and a highly efficient conductive network, but also became a preferred channel for the penetration of corrosive media and a weak point in mechanical properties. At the same time, the uneven dispersion also affected the distribution of microcapsules, making it impossible to reliably trigger their function. In contrast, Comparative Example 2, by replacing the flake zinc powder with ordinary spherical zinc powder, resulted in a decrease in the shielding performance of the coating. This is because the spherical zinc powder particles are randomly stacked in the coating, making it difficult to form a dense physical barrier layer with overlapping and parallel arrangement like the flake zinc powder. This greatly shortens the penetration path of water, oxygen, and corrosive ions, weakening the passive physical shielding ability of the coating. In contrast, Comparative Example 3, lacking the addition of polyacrylate solution (leveling agent), resulted in insufficient uniformity of the paint film. This was due to the absence of a highly efficient leveling agent, leading to uneven surface tension during the curing process, reduced flow and spreading ability, and a tendency to form microscopic thickness variations, orange peel texture, or localized weak points. These microscopic defects become corrosion initiation points in salt spray environments, compromising the overall integrity and protection of the coating. Furthermore, the absence of leveling agent also affected the uniform distribution of internal stress in the paint film, resulting in localized stress concentration upon impact, manifesting as whitening. This indicates that its mechanical reliability was already at the edge of acceptable levels.

[0041] Those skilled in the art should understand that the discussion of any of the above embodiments is merely exemplary and is not intended to imply that the scope of the invention is limited to these examples; within the framework of the invention, the technical features of the above embodiments or different embodiments can also be combined, the steps can be implemented in any order, and there are many other variations of the different aspects of the invention as described above, which are not provided in detail for the sake of brevity.

[0042] This invention is intended to cover all such substitutions, modifications, and variations that fall within the broad scope of the appended claims. Therefore, any omissions, modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of this invention should be included within the scope of protection of this invention.

Claims

1. A novel recyclable paint, characterized in that, It is composed of the following components in parts by weight: 40-50 parts modified epoxy resin, 5-10 parts reactive diluent, 12-18 parts bismaleimide, 1-3 parts amino-modified multi-walled carbon nanotubes, 5-10 parts flake zinc powder, 8-12 parts corrosion-responsive capsules, 5-8 parts curing capsules, 0.5-1.5 parts wetting and dispersing agent, 0.1-0.2 parts leveling agent, 0.2-0.8 parts defoamer, and 3-8 parts zinc phosphate pigment; The modified epoxy resin is a furfurylamine-modified epoxy resin; The wetting and dispersing agent is BYK-163; The leveling agent is a polyacrylate solution; The defoamer is BYK-055.

2. The novel recyclable paint according to claim 1, characterized in that, The modified epoxy resin is prepared in the following steps: Under a nitrogen atmosphere, triphenylphosphine catalyst and anhydrous propylene glycol methyl ether acetate solvent were added to epoxy resin and stirred at 200-300 rpm for 20-30 min. Furfurylamine was added, the temperature was raised to 60-70℃, and the reaction was stirred at 300-400 rpm for 4-6 h to obtain a mixture. The mixture was then cooled to 60-70℃ and vacuum dried for 2-4 h to obtain modified epoxy resin. The mass ratio of the epoxy resin, anhydrous propylene glycol methyl ether acetate solvent, and triphenylphosphine catalyst is 1:0.2-0.3:0.003-0.

005.

3. The novel recyclable paint according to claim 1, characterized in that, The preparation steps of the reactive diluent are as follows: Furfuryl alcohol and the catalyst tetrabutylammonium bromide were added to epichlorohydrin, heated to 63-67℃, stirred at 300-350 rpm for 3-4 hours until the reaction was complete, cooled to 0-4℃, and 30wt% sodium hydroxide solution was added. The mixture was stirred at 400-500 rpm for 1-2 hours, heated to 25-30℃, and stirred for 2-3 hours. Deionized water was added, and the mixture was stirred at 200-250 rpm for 12-14 hours. The mixture was then vacuum distilled to obtain the active diluent. The mass ratio of furfuryl alcohol, the catalyst tetrabutylammonium bromide, epichlorohydrin, 30wt% sodium hydroxide solution, and deionized water is 1:0.04-0.05:1.3-1.4:3-4:4-5.

4. The novel recyclable paint according to claim 1, characterized in that, The corrosion-responsive capsule is prepared using the following steps: Step A1: Add gelatin and gum arabic to deionized water, heat to 50-54℃, stir at 100-200 rpm for 10-12 minutes, add 1wt% glacial acetic acid to adjust the pH to 4-4.5, add Tween-80 to obtain the aqueous phase; Step A2: Add benzotriazole and monomaleimide monomers to ethyl acetate, stir at 100-200 rpm for 10-12 min to obtain the oil phase; Step A3: Add the oil phase to the aqueous phase, stir at 1000-1500 rpm for 10-16 min, add deionized water, heat to 50-54℃, stir at 400-450 rpm for 10-12 min, cool to 8-10℃, add 25wt% glutaraldehyde solution, stir at 400-500 rpm for 2-4 h, add sodium hydroxide to adjust the pH to 9.0-9.5, stir for 1-1.2 h, wash, filter, and vacuum dry for 22-24 h to obtain corrosion-responsive capsules.

5. A novel recyclable paint according to claim 4, characterized in that, The mass ratio of gelatin, gum arabic, and Tween-80 in step A1 is 1:1-1.2:0.05-0.07; The mass ratio of benzotriazole, monomaleimide monomer to ethyl acetate in step A2 is 1:0.3-0.4:10-12; The mass ratio of the oil phase, aqueous phase, deionized water, and 25wt% glutaraldehyde solution in step A3 is 1:9-10:8-9:0.05-0.

06.

6. The novel recyclable paint according to claim 1, characterized in that, The steps for preparing the solidified capsule are as follows: Step B1: Add urea to a 37wt% formaldehyde solution, add 10wt% sodium hydroxide solution to adjust the pH to 8.0-8.5, heat to 65-75℃, stir at 300-400 rpm for 1-1.2 hours to obtain urea-formaldehyde resin prepolymer; Step B2: Add sodium dodecylbenzenesulfonate to deionized water, add 2wt% polyvinyl alcohol solution, stir at 100-200 rpm for 10-12 hours to obtain an emulsified aqueous phase; Step B3: Add the boron trifluoride-monoethylamine complex to dibutyl phthalate, add the emulsified aqueous phase, stir at 1500-2000 rpm for 10-12 min, heat to 50-60℃, add urea-formaldehyde resin prepolymer, add 10wt% ammonium chloride solution to adjust the pH to 3.5-4.0, add resorcinol, stir at 300-500 rpm for 2-3 h, wash, filter, and vacuum dry for 22-24 h to obtain cured capsules.

7. A novel recyclable paint according to claim 6, characterized in that, The mass ratio of urea to 37wt% formaldehyde solution in step B1 is 1:2-3; In step B2, the mass ratio of sodium dodecylbenzenesulfonate, deionized water, and 2wt% polyvinyl alcohol solution is 1:300-350:100-120. The mass ratio of boron trifluoride-monoethylamine complex, dibutyl phthalate, emulsified aqueous phase, urea-formaldehyde resin prepolymer, and resorcinol in step B3 is 1:5-6:40-50:10-12:0.02-0.

03.

8. A method for preparing a novel recyclable paint according to any one of claims 1-7, characterized in that, The preparation steps are as follows: Step S1: Add BYK-163 to modified epoxy resin a, heat to 25-35℃, stir at 300-500 rpm for 3-5 minutes, add amino-modified multi-walled carbon nanotubes and flake zinc powder, stir at 2500-3000 rpm for 20-30 minutes to obtain slurry; Step S2: Add modified epoxy resin b, reactive diluent and bismaleimide to the slurry, rotate at 1000-1200 rpm, heat to 25-35℃, stir for 16-20 minutes to obtain the base paint; Step S3: Add the corrosion-responsive capsules and curing capsules to the base paint, stir at 150-300 rpm for 10-16 min, add polyacrylate solution, BYK-055 and zinc phosphate pigment, stir for 10-12 min, reduce the pressure to -0.09 to -0.095 MPa, stir at 300-500 rpm for 10-16 min, and pass through a 150-mesh sieve to obtain a recyclable new paint.

9. The method for preparing a novel recyclable paint according to claim 8, characterized in that, The mass ratio of BYK-163, modified epoxy resin a, amino-modified multi-walled carbon nanotubes and flake zinc powder in step S1 is 1:25-27:2-3:7-9; In step S2, the mass ratio of the modified epoxy resin b, reactive diluent, bismaleimide, and slurry is 1:0.2-0.4:0.5-0.7:1.3-1.

5. The mass ratio of the corrosion-responsive capsule, curing capsule, base paint, polyacrylate solution, BYK-055, and zinc phosphate pigment in step S3 is 1:0.6-0.7:8-9:0.02-0.04:0.02-0.04:0.5-0.

6.

10. Application of a novel recyclable paint, using a novel recyclable paint as described in any one of claims 1-9, characterized in that, The recyclable new paint is used in aerospace equipment, high-end automobile bodies and chassis, and electrical equipment housings.